2008
DOI: 10.1111/j.1365-2621.2007.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cream treatment on phospholipids and protein recovery in butter‐making process

Abstract: A simple approach is proposed to recover native protein and phospholipid fractions from butter-making process using equipments available in dairy-processing plant. A washing treatment was used to remove protein from the cream and increase the phospholipids purity in buttermilk. Cream from a first separation was diluted with milk ultrafitration permeate and separated a second time. A 10X dilution factor reduced protein concentration in the cream from 1.6 ± 0.2 to 0.52 ± 0.03%. As a result, the phospholipids to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 25 publications
8
44
1
2
Order By: Relevance
“…The average chemical composition of Buttermilk samples are represented in Table (3). It was found that the maximum value of moisture content for investigated Buttermilk samples was 95.00 %, and the minimum value was 89.22% with a mean of 92.45%.The present data are in agreement with these of Lonkar et.al., (2011), who found that the average value was 92.44±1.06%.These results are differ from that of Britten et. al.,(2008), who found that, the maximum value for moisture content was 92.00% and the minimum was 88.00% for sweet Buttermilk and with that of Bakry et.al.,(2011),who found that the average values were 93.71±1.52 and 94.68±0.54 for buffalo and cow Buttermilk respectively.…”
Section:  the Chemical Composition Of Rayeb Milk Samplescontrasting
confidence: 57%
“…The average chemical composition of Buttermilk samples are represented in Table (3). It was found that the maximum value of moisture content for investigated Buttermilk samples was 95.00 %, and the minimum value was 89.22% with a mean of 92.45%.The present data are in agreement with these of Lonkar et.al., (2011), who found that the average value was 92.44±1.06%.These results are differ from that of Britten et. al.,(2008), who found that, the maximum value for moisture content was 92.00% and the minimum was 88.00% for sweet Buttermilk and with that of Bakry et.al.,(2011),who found that the average values were 93.71±1.52 and 94.68±0.54 for buffalo and cow Buttermilk respectively.…”
Section:  the Chemical Composition Of Rayeb Milk Samplescontrasting
confidence: 57%
“…Repeated washing with water multiplied this effect, and loosely bound components on the outer side of the MFGM or larger MFGM fragments were released into the skim milk. Britten et al (2008) reported a decrease of 20% of the phospholipid content of the cream after the first wash. Additional washing treatments further reduced the phospholipid concentration by about 10% for each cycle. Morin, Britten, Jim enezFlores, and Pouliot (2007a) compared buttermilk samples from native and washed cream and found that the relative phospholipid content decreased by almost 60% (absolute from 0.13% to 0.05%) after just one washing step.…”
Section: The Impact Of Washing On Fat Globules and The Mfgmmentioning
confidence: 96%
“…Britten et al (2008) diluted raw cream (45e50% fat) by a factor of ten and applied additional separation steps to produce washed cream. Fat globule size was increased by 12% after each washing step.…”
Section: The Impact Of Washing On Fat Globules and The Mfgmmentioning
confidence: 99%
“…However, the sweet buttermilk fat composition is generally dominated by neutral lipids (TAGs up to 60-70% of the fat content), which originate from the lipid core of the milk fat globule membranes, while PLs account for 15-30% by weight [29]. The levels of buttermilk PE, PC and SM range between 39-40%, 24-25% and 18-20%, respectively, while phosphatidylserine (PS) and PI occur at 8-9% each of total PLs [30]. Buttermilk also contains variable amounts of sialylated (N-acetylneuraminic acid derivatives, Neu5Ac) glycolipids, generally referred to as gangliosides (0.5-2% of total lipids), the most abundant being GD3 (Neu5Ac-Neu5Ac-galactose-glucose-ceramide) and GM3 (Neu5Ac-galactose-glucose-ceramide).…”
Section: Resultsmentioning
confidence: 99%